Juridical Analysis of Nurses' Knowledge of Legal Responsibility for Medical Actions Based on Delegation of Doctors at Korbafo Health Center - Fransita M. A Fiah; Emanuel S.B Lewar; Irlin Falde Ritti (Soepra Jurnal Hukum Kesehatan, 2022)
Abstract: The shortage of medical personnel (doctors) creates a situation that requires nurses to take medical actions or take medical actions that are not under their authority. These actions are carried out with or without the delegation of authority from other health workers including doctors so that it can cause legal problems related to responsibilities that are imposed unilaterally and can be detrimental to nurses. Based on the Strategic Plan of the Rote Ndao District Health Office for 2019-2024, in 2018 the ratio of specialists is 1:79,807 population, the ratio of general practitioners is 1: 12,278 population, the ratio of dentists is 1: 26,602 population and in total the ratio of medical personnel is 1: 7,501 residents. If referring to the national target according to the health workforce development plan for 2011-2025, the standard ratio of specialist doctors is 1:10,000 population, the ratio of general practitioners is 1:2,500 population and the ratio of dentists is 1:1,833 population and the ratio of medical personnel is 1:632 population. . Every state and government administration must have legitimacy, namely the authority granted by law. In administrative law, there are 3 (three) sources of authority, namely attribution, delegation, and mandate. Health services by health workers recognize the delegation of authority, which is commonly known as the delegation of authority. The practice of delegation of authority (delegation of authority) involves the nursing community, which occurs both in nursing services and in health care practices. The delegation of authority is understood as the delegation of doctors to nurses to carry out certain medical tasks. This study aims to analyze the knowledge of nurses about legal responsibilities in carrying out actions based on the delegation of doctors at Korbafo Health Center and analyze the implementation of delegation of medical actions by doctors to nurses at Korbafo Health Center. The approach method used is empirical legal research. This type of research is descriptive and qualitative. This research for novice lecturers will increase the knowledge and competence of researchers in developing research and national publications. The research output is in the form of articles in Indonesian nursing and health law journals.Keywords: Nurse knowledge, legal responsibility, medical action and delegation  Abstrak: Keterbatasan tenaga medis (dokter) menimbulkan situasi yang mengharuskan perawat melakukan tindakan pengobatan atau melakukan tindakan medis yang bukan wewenangnya. Tindakan tersebut dilakukan dengan atau tanpa adanya pelimpahan wewenang dari tenaga kesehatan lain termasuk dokter, sehingga dapat menimbulkan permasalahan hukum terkait dengan tanggung jawab yang dibebankan sepihak dan bisa merugikan perawat. Berdasarkan Rencana Strategis Dinas Kesehatan Kabupaten Rote Ndao Tahun 2019-2024 adalah Pada tahun 2018 rasio dokter spesialis sebesar 1 :79.807 penduduk, rasio dokter umum sebesar 1 : 12.278 penduduk, rasio dokter gigi sebesar 1 : 26.602 penduduk dan secara total rasio tenaga medis 1:7.501 penduduk. Jika mengacu pada target nasional menurut rencana pengembangan tenaga kesehatan tahun 2011-2025, standar rasio dokter spesialis sebesar 1:10.000 penduduk, rasio dokter umum 1:2.500 penduduk dan rasio dokter gigi sebesar 1:1.833 penduduk dan rasio tenaga medis sebesar 1:632 penduduk. Setiap penyelenggaraan kenegaraan dan pemerintahan harus memiliki legitimasi, yaitu kewenangan yang diberikan oleh undang-undang. Dalam hukum Administrasi, dikenal 3 (tiga) sumber kewenangan, yaitu atribusi, delegasi, dan mandat. Pelayanan kesehatan oleh tenaga kesehatan mengenal adanya pelimpahan wewenang, yang biasa dikenal dengan delegasi wewenang. Praktik pelimpahan wewenang (delegasi wewenang) tersebut melibatkan komunitas perawat, yang terjadi baik pada pelayanan keperawatan maupun praktik pelayanan kesehatan. Delegasi wewenang tersebut dipahami sebagai pelimpahan dari dokter kepada perawat untuk melaksanakan tugas medis tertentu. Penelitian ini bertujuan untuk menganalisis pengetahuan perawat tentang tanggung jawab hukum dalam melakukan tindakan berdasarkan delegasi dokter di Puskesmas Korbafo dan menganalisis pelaksanaan delegasi tindakan medis oleh dokter kepada perawat di Puskesmas Korbafo. Metode pendekatan yang digunakan yaitu penelitian hukum empiris. Jenis penelitian ini adalah deskriptif kualitatif. Penelitian dosen pemula ini akan meningkatkan pengetahuan dan kompetensi dari peneliti dalam mengembangkan penelitian dan publikasi nasional. Luaran penelitian berupa artikel pada jurnal keperawatan dan hukum kesehatan Indonesia.Kata kunci : Pengetahuan perawat, tanggung jawab hukum, tindakan medis  dan delegasi